The writer's handbook. - Houghton, Samuel G. (Samuel Gilbert) 1902-1975.; Olsen, Udia G.; Burack, A. S. (Abraham Saul) 1908-.; Kamerman, Sylvia E.; Abbe, Elfrieda (Boston Writer, Inc., 1936)
"Manuscript market section", ed. by U.G. Olsen, 1941-44; by E.P. Werby, 1945-
Editors: S.G. Houghton, U.G. Olsen, 1936-1940; A.S. Burack, 1941-1978; Sylvia K. Burack, 1978-2001; Elfrieda Abbe, 2002-
Published: Waukesha, WI : The Writer Books, 2002-2005.
Also issued online.
"Articles ... were, for the most part, originally published in the Writer."
Keywords: Authorship -- Handbooks, manuals, etc; Publishers and publishing; Art d'eÃÅcrire -- Guides, manuels, etc; EÃÅdition -- PeÃÅriodiques